La promotion du « dialogue social » dans l’entreprise. Loi Rebsamen et rapport Combrexelle - Sylvaine Laulom; Cécile Nicod; Arnaud Mias; Cécile Guillaume; Jean-Michel Denis; Paul Bouffartigue (La Nouvelle Revue du Travail)
In late summer 2015, two published texts marked a significant move to promote collective bargaining and “social dialogue” in companies. On 17 August, France’s so-called “Rebsamen” law was enacted, aimed at “improving the efficiency and quality of social dialogue in companies”. In early September, Jean-Denis Combrexelle, a former Director-General for Work, submitted a report featuring a long list of proposals for galvanising negotiations and “broadening [their] scope”. Some fed into the spring 2016 Work bill, who first draft met with opposition from all French employee unions.To understand everything at stake in these texts along with the perspectives they have opened up, two legal specialists in this field agreed to be interviewed by us. Their transcripts offer an overview of some major changes affecting company health and safety committees, the agreement to host single worker delegations, worker representation in micro-enterprises, anti-union discrimination and professional equality. It also looks at the major transformations that the French industrial relations system is going through at present, with Sylvaine Laulom and Cécile Nicod specifically highlighting the fact that widespread support for collective bargaining today can mainly be attributed to the assumption that this will produce certain outcomes enhancing business competitiveness. They also note that the debate about the simplification of labour law masks ongoing developments relating to “simpler obligations for employers, meaning a re-balancing of their power vis-a-vis employees, something hiding both sides’ real negotiating positions”.